Oil yield components and oil quality of high stearic-high oleic sunflower genotypes as affected by intercepted solar radiation during grain filling - Martínez, Roberto Dionisio (2012)
High stearic-high oleic sunflower oil presents high thermal stability. This oil is an alternative to the hydrogenation process which produces trans fatty acids. The effect of intercepted solar radiation (ISR) per plant during grain filling on oil yield components and oil fatty acid composition was investigated in three sunflower high stearic-high oleic genotypes. Three field experiments were conducted and treatments to modify ISR per plant were applied during grain filling: shading, defoliating and thinning plants. Increasing ISR per plant linearly increased grain number per capitulum, weight per grain and in some cases palmitic and stearic acid percentages. In the hybrid, grain oil percentage and oleic acid concentration increased with a decreasing rate, reaching a maximum value at high levels of ISR per plant. Linoleic acid percentage decreased with a decreasing rate, reaching a minimum value at high levels of ISR per plant. Oil yield components presented heterosis. This information contributes to explain the effects of environment on yield and oil quality in high stearic-high oleic genotypes and could be used to design management practices that optimise these traits.